(untitled) (International Journal of Geoscience, Engineering and Technology, 2021)
This work aims to contribute to the study and analysis of the stability of dams in Brazil and in the world, in addition to studying the reasons for their failure, from a literary review, with important data and information. It is worth mentioning that once a dam breaks, it causes immeasurable impacts such as environmental, economic and social damage to the population, in addition to the loss of life. Here we will explain about liquefaction, overtopping and plumbing, explaining each of these phenomena and we will mention cases of ruptures with their respective causes, thus making a literary review of each case. The intention is to study the safety of dams in view of the great increase in cases of disruption, which have generated major accidents with thousands of victims worldwide, knowing that when these undertakings are taken seriously, we can drastically reduce their likelihood of disruption.